Psychology without foundations history, philosophy and psychosocial theory - Brown, Steven D., Dr.; Stenner, Paul.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
Social psychology has been deemed a discipline 'in crisis'. This title proposes a way out of the crisis by letting go of the idea that psychology needs 'new' foundations or a new identity whether biological, discursive or cognitive.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social psychology -- Philosophy; Electronic books